2011
DOI: 10.1177/0022219410392043
|View full text |Cite
|
Sign up to set email alerts
|

Students With Reading and Spelling Disabilities

Abstract: The present study investigated whether the members of adolescents' peer groups are similar in reading and spelling disabilities and whether this similarity contributes to subsequent school achievement and educational attainment. The sample consisted of 375 Finnish adolescents whose reading and spelling disabilities were assessed at age 16 with the Finnish dyslexia screening test. The students also completed a sociometric nomination measure that was used to identify their peer groups. Register information on pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
12
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 46 publications
3
12
0
Order By: Relevance
“…We also found a significant, albeit small, correlation between social capital-student ranking and academic achievement, consistent with previous research in which adolescents (e.g., Kiuru et al, 2011;Nichols & White, 2001) and graduate students (i.e., Lomi et al, 2011) from the same peer group shared a similar level of academic achievement, suggesting social selection. However, unlike in Lomi et al's (2011) study that found students to assimilate to the academic performance of their ties-having ties with performance higher than oneself provided an upward pull-we failed to find support that having higher achieving student social ties explained academic achievement for university students with RD.…”
Section: Discussionsupporting
confidence: 91%
“…We also found a significant, albeit small, correlation between social capital-student ranking and academic achievement, consistent with previous research in which adolescents (e.g., Kiuru et al, 2011;Nichols & White, 2001) and graduate students (i.e., Lomi et al, 2011) from the same peer group shared a similar level of academic achievement, suggesting social selection. However, unlike in Lomi et al's (2011) study that found students to assimilate to the academic performance of their ties-having ties with performance higher than oneself provided an upward pull-we failed to find support that having higher achieving student social ties explained academic achievement for university students with RD.…”
Section: Discussionsupporting
confidence: 91%
“…Apparently in small-group teaching settings, for low and average achieving students, friendship does not contribute to their study success. Building friendships or belonging to a peer group often is based on similar characteristics (McPherson, Smith-Lovin, & Cook, 2001) and achievement levels (Flashman, 2012;Kiuru et al, 2011;Nichols & White, 2001). According to Lomi et al (2011), it is more likely that students become friends when they are similar in their achievement level, but students also become more similar in their achievement levels over time.…”
Section: Discussionmentioning
confidence: 99%
“…Reading fluency was measured with three tests. Two word reading tests – the Word Identification and Spelling Errors tests (Holopainen et al 2004; Kiuru et al 2011)—and one sentence reading test – the Salzburg Reading Fluency Test (Landerl et al 1997; translated into Finnish by Sini Huemer)—were used.…”
Section: Methodsmentioning
confidence: 99%